Reversal of Loperamide Induced Intestinal Smooth Muscle Relaxation by Glibenclamide and Repaglinide in Vitro (Medical Forum Monthly, 2024)
Objective: To compare the inhibitory effects of Glibenclamide and Repaglinide on loperamide induced relaxation of isolated ileum of Rabbit.Study Design: Comparative controlled in-vitro experimental Study.Place and Duration of Study: This study was conducted at Department of Pharmacology, Yusra Medical & Dental College Islamabad from February to April 2014.Materials and Methods: Isolated pieces of small intestine of rabbits placed in freshly prepared Tyrode nutritional solution. Six groups were designed. In group I, effect of Acetylcholine on the intestine was observed. In group II ileum was exposed to serial dilutions of acetyl choline in the presence of fixed concentration of loperamide 10-6, dose response curve was plotted. In group III fixed dose of Glibenclamide 10-6 was given and dose response curve was plotted with Acetylcholine. In group IV fixed dose of Repaglinide 10-6 was given and dose response curve was plotted with Acetylcholine. Group V was given Loperamide+Glibenclamide and dose responce curve was plotted with Acetylcholine, while group VI was given Loperamide+Repaglinide and dose response curve was plotted with Acetylcholine. The effects were observed and recorded on Power lab .Results: Acetyl choline has produced dose dependent increase in force of contraction from 4.9 to 7.2 mN. In the presence of glibenclamide the force of intestinal smooth muscle contraction increase from 6.4 to 7.8mN and in the presence of loperamide the force decreased from 4.8 to 3.03mN. In the end effect observed with acetyl choline in the presence of loperamide and glibenclamide is 6.5 to 7.7mN. Similarly with repaglinide alone the force of contraction increased from 5.4 to 9.6mN and with repaglindie + loperamide from 4.3 to 21.5 mN. On statistical analysis ‘t’ test was applied and P value was found to be significant that is P<0.05.The dose response curve of acetylcholine on intestinal smooth muscle of rabbit shifted towards left side with glibenclamide and rapaglinide alone. In the presence of Loperamide the curve shifted towards right side. Glibenclamide and repaglinide when given together with loperamide respectively lead to leftwards shift of the dose response curve.Conclusion: Hence sulfonylurea glibenclamide and repaglinide, the oral anti-diabetics effectively reversed the relaxation of intestinal smooth muscle by loperamide.